School design: opportunities through collaboration - Parnell, Rosie; Cave, Vicky; Torrington, Judith (CoDesign, 2008)
This paper explores the process of involving the whole school community, especially teachers and students, in the design of schools. A series of semi-structured interviews were conducted with a range of professionals who have worked with target users in this development process. The interviews were transcribed and then common themes from each of the interviews were developed. Findings suggest that a host of opportunities arise from the special mix of different processes, professions and people involved in school design, but that these are not always being recognised or exploited. The need to acknowledge the opportunities which lie within the process and to not just be fixed on the product - the finished school - appears to be significant. It transpires that the perception of the process from the different perspectives of all involved has an impact on the way in which the process unfolds. The proposed outline model conceptualises the school design process as a collection of opportunities which can arise from collaborative working. Suggestions are made for further research.